2005
DOI: 10.1227/01.neu.0000180030.00167.b9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Electrode Design: A Prospective, Randomized, Controlled Trial Comparing Percutaneous with Laminectomy Electrodes: Part II–Clinical Outcomes

Abstract: Laminectomy electrode placement, although more invasive than percutaneous placement, yields significantly better clinical results in patients with failed back surgery syndrome at mean 1.9 years follow-up. In our small sample, however, the statistical significance of this advantage disappeared at mean 2.9 years follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 39 publications
0
124
0
1
Order By: Relevance
“…46 During programming, the stimulation is initiated at 1 mA, with the pulse width fixed at 300 μsec, and increased until an improvement is noted by the patient. Once the patient experiences a difference in the tinnitus percept, the amplitude, pulse width, and frequency are adjusted by increasing and decreasing the individual parameters to what yields best suppression of the phantom percept.…”
Section: Discussionmentioning
confidence: 99%
“…46 During programming, the stimulation is initiated at 1 mA, with the pulse width fixed at 300 μsec, and increased until an improvement is noted by the patient. Once the patient experiences a difference in the tinnitus percept, the amplitude, pulse width, and frequency are adjusted by increasing and decreasing the individual parameters to what yields best suppression of the phantom percept.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that placement of wire leads has been in clinical use for several decades for control of spasticity and pain, including failed back surgery syndrome and radicular pain syndrome. [30][31][32][33][34][35][36] A clinical trial of this technology will be necessary, however, to establish the safety and efficacy of this method in persons with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…31 No superiority of SCS over control (2B−) was noted when comparing laminectomy to percutaneous electrodes, 26 SCS to repeat lumbosacral surgery, or burst stimulation to 500-Hz or sham stimulation ( 28 found that position-adaptive stimulation provided a 69% patient-perceived improvement in activity, a 57.8% improvement perceived in the control group, and a 47.9% patient-rated improvement in sleep, when compared with manually adjusted stimulation ( Table 3).…”
Section: Functional Capacitymentioning
confidence: 99%
“…24,[26][27][28][29][30][31] Outcomes-specific data are reported in Table 3. The earliest study, by North et al, 24 in 2005, compared SCS with repeated lumbosacral spine surgery for FBSS patients, which yielded a difference of 35.8% (P < 0.01) in the primary outcome (≥50% pain relief ) favoring the SCS group at 3 years' follow-up, albeit with a small sample size in a single center.…”
Section: Perceived Pain Relief or Change In Pain Scorementioning
confidence: 99%